Konsep Diri Penderita TB Paru dengan Karies Gigi di Wilayah Kerja UPT Puskesmas Ambunten Kecamatan Ambunten Kabupaten Sumenep - Emdat Suprayitno; Mujib Hannan; Ummi Afifah (Fakultas Kedokteran Gigi Universitas Jember, 2020)
Pulmonary TB is still a major global health problem. It causes ill-health among millions of people every year and ranks the second leading cause of death from infectious diseases worldwide after Human Immunodeficiency Virus. This disease can affect anyone and can cause physical, mental, and social changes. This situation can affect the sufferer's self-concept. The purpose of this study was to determine how many TB patients with dental caries experienced impaired self-concept. Design This research is a quantitative descriptive study using a cross-sectional non-analytic design. The population in this study were all 64 patients with pulmonary tuberculosis with dental caries, using a total sampling technique. The variable in this study was the self-concept of pulmonary tuberculosis patients with dental caries.The results showed that patients with pulmonary tuberculosis in the Work Area of the Ambunten Health Center, Ambunten District, Sumenep Regency in 2018, showed that of the 64 respondents studied had a self- concept disorder where most 36 people (56%) experienced negative self-concept and 28 people (43.8%) had a conceptual disorder. positive self. The conclusion of the self-concept study of pulmonary tuberculosis patients is that most people who suffer from pulmonary TB disease still experience negative self-concept disorders.